Evaluation of phytase super dosing and its combinations with other additives as an alternative to antibiotic growth promoters in broiler chickens reared in a deep litter system - Paul, Shyam Sundar; Rao, Savaram Venkata Rama; Chatterjee, Rudra Nath; Raju, Mantena Venkata Lakshmi Narasimha; Prakash, Bhukya; Yadav, Satya Pal; Kannan, Alagarsamy; Reddy, Godumagadda Narender; Kumar, Vikas; Kumar, Prakki Santosh Phani (Frontiers in Animal Science, 2025)
IntroductionAntimicrobial growth promoters (AGPs) have traditionally been used in chicken production to improve performance. However, such products may promote the development and spread of antimicrobial resistance genes (ARGs), which is of huge societal concern. The evaluation of newer feed additives as an alternative to AGPs for broiler chickens in terms of their effect on gut microbes and resistome profile besides effectiveness under challenging housing systems like deep litter systems under tropical conditions is urgently needed.MethodsWe investigated the comparative efficacy of phytase super dosing (P, phytase at 2,000 FTY/kg feed) alone and its combinations with other feed additives, namely phytase plus butyrate (PB, phytase 2,000 FTU/kg feed plus encapsulated sodium butyrate 500g/t feed), phytase plus essential oil (EO) (PE, phytase 2,000 FTU/kg feed plus encapsulated essential oil 400g/t feed), and phytase plus probiotic Bacillus subtilis (PBS, phytase 2,000 FTU/kg feed plus B. subtilis 400g/t feed) as alternatives to AGPs alongside two control groups, namely an AGP, bacitracin methylene disalicylate, (B, 500 g/t feed) and negative control (C), on growth, immunity, feed efficiency, and survivability under a deep litter system of rearing. We also compared the gut microbiome and resistome profile in the bestperforming treatment group and control groups.ResultsAt day 35, broilers fed the phytase alone or in combination with butyrate, EO, or B. subtilis had significantly higher cumulative performance in terms of feed efficiency than those fed B or C with the best feed efficiency recorded in the PE group. Overall, the cumulative average mortality rates were 4.57%, 4.0%, 5.14%, 6.28%, 2.86%, and 1.71% in the C, B, P, PB, PE, and PBS groups, respectively. The supplementation of phytase at a super dosing level plus encapsulated EO resulted in a significant increase in the relative abundance of beneficial bacteria in the gut compared to the controls. The density of ARG or mobile genetic elements was not influenced by treatments.DiscussionThe study showed that phytase super dosing alone delivered better feed efficiency in broiler chickens compared to the control or AGP, and encapsulated EO or B. subtilis plus phytase super dosing can reduce the mortality rate.